(untitled) (Journal of Civil Engineering Researchers, 2022)
Steel shear walls have always been used in the construction and improvement of many structures due to their advantages such as high strength and stiffness, ductility and excellent energy absorption. In the meantime, corrugated steel shear walls have been proposed due to postponing the elastic buckling of the plate and increasing ductility and energy absorption. Corrugated steel shear walls can be used in both single and double layers. Due to the fact that so far, limited research has been conducted about double corrugated steel shear walls, therefore, in this research, the hysteresis behavior of double and single layer corrugated steel shear walls has been analyzed parametrically using the finite element method and using ABAQUS software. Thus, after validating a experimental sample, a two-layer corrugated steel shear wall with one bay-one story with conventional angles of 30, 45 and 60 degrees was investigated in ABAQUS software under cyclic loading. The results of this research showed that the hysteresis curve of double and single layer corrugated steel shear walls is stable. Also, the resistance and energy absorption of double corrugated steel shear walls is higher than single layer corrugated wall. Also, the resistance of corrugated steel shear walls with single and double layers is lower than that of flat steel shear walls. Also, increasing the corrugation angle of the plate has led to an increase in resistance and energy absorption. In addition, behavior factor and ductility of flat steel shear walls are higher than single-layer and double corrugated walls. Nevertheless, the over- strength factor of the studied samples is almost equal to each other.